A sensitive determination of lead by hydride generation integrated with micro-sampling gas–liquid separator-FAAS after preconcentration by NiFe2O4 nanoparticles - Merve Fırat Ayyıldız; Süleyman Bodur; Sezgin Bakırdere (Scientific Reports)
Abstract In the present study, dispersive solid phase extraction – hydride generation integrated with micro–sampling gas–liquid separator – flame atomic absorption spectrometry was proposed to determine lead in lake water samples taken in the Horseshoe Island, Antarctica. In scope of this study, microwave assisted NiFe2O4 nanoparticles were synthesized, and the characterization of nanoparticles were carried out by FT-IR, XRD and SEM. All influential parameters of dispersive solid phase extraction and hydride generation were optimized to enhance signal intensity belonging to the analyte. System analytical performance studies were performed, and limit of detection and limit of quantitation were calculated as 2.16 µg kg–1 and 7.19 µg kg–1, respectively. Recovery studies were conducted to the spiked lake water samples and two different calibration strategies were applied. Percent recovery results were calculated between 102.0 and 169.5% by external calibration strategy while matrix matching calibration strategy provided recovery results in the range of 78.8–142.9%.